2012
DOI: 10.1159/000330258
|View full text |Cite
|
Sign up to set email alerts
|

Identity and Eating Disorders (IDEA): A Questionnaire Evaluating Identity and Embodiment in Eating Disorder Patients

Abstract: Background: In this paper we tested the hypothesis that persons with eating disorders (EDs) are affected by disturbances of the way they experience their own body (embodiment) and shape their personal identity, assuming that the various kinds of anomalies of eating behavior are consequences thereof. Sampling and Methods: We developed and validated a new self-reported questionnaire named IDEA (IDentity and EAting disorders), which was administered to 147 ED patients and 187 healthy controls. Test-retest reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
102
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(113 citation statements)
references
References 72 publications
8
102
0
3
Order By: Relevance
“…Both these hypotheses are grounded in the existing literature. The assumption that these patients do not ‘feel' themselves - and especially their own body and emotions - is in accordance with most of the literature on the psychopathology of eating disorders and, especially, with the emphasis given in body and specific cognitive and emotional disturbances [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20] to enhancing the vulnerability to eating disorders. The concept that eating disorders stem from identity impairments is also firmly grounded in the theoretical literature [21,22,23,24,25].…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Both these hypotheses are grounded in the existing literature. The assumption that these patients do not ‘feel' themselves - and especially their own body and emotions - is in accordance with most of the literature on the psychopathology of eating disorders and, especially, with the emphasis given in body and specific cognitive and emotional disturbances [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20] to enhancing the vulnerability to eating disorders. The concept that eating disorders stem from identity impairments is also firmly grounded in the theoretical literature [21,22,23,24,25].…”
Section: Introductionsupporting
confidence: 80%
“…In a previous study, we showed that in patients suffering from eating disorders, the lived body is no longer direct first-personal experiential evidence, but it is an entity that exists as viewed from an external perspective [18]. This view from without on one's body can be described in terms of the Sartrean concept of ‘the body for the other'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jean Paul Sartre extends this to distinguish between the lived body (body-subject) and the physical body (body-object) -when one becomes aware of the body-object being looked at by the other, it becomes the "lived body for others" [7]. Embodiment theory considers an individual's connection to, awareness of, and satisfaction with their own body.…”
Section: Introductionmentioning
confidence: 99%
“…Embodiment theory considers an individual's connection to, awareness of, and satisfaction with their own body. Disturbances to one's experience of embodiment are implicated in the eating disordered subject [7].…”
Section: Introductionmentioning
confidence: 99%